MATHEMATICAL MODEL TO DIAGNOSE OPERATING POWERFUL ELECTRICAL MACHINE INSULATION STATE USING THERMAL IMAGE - Grabko, Volodymyr; Grabko, Valentyn (Scientific Works of Vinnytsia National Technical University, 2015)
The paper presents both the approach and the mathematical model to find a possible powerful electrical machine windings insulation damage place, from the points inaccessible for thermal viewing.